2002
DOI: 10.1038/sj.npp.1300092
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter: A Potential Substrate in the Biology of Suicide

Abstract: Suicide is a serious public health problem in the US, yet its neurobiological underpinnings are poorly understood. Suicide is highly correlated with depressive symptoms, and considerable evidence suggests that depression is associated with a relative deficiency in serotonergic neurotransmission. Serotonergic circuits also mediate impulsivity, a trait obviously relevant to suicide. These findings, taken together, suggest that alterations in the serotonergic system might contribute to suicidal behavior, serving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 70 publications
0
62
1
2
Order By: Relevance
“…Since the demonstration of decreased levels of 5-hydroxyindoleacetic acid (5-HIAA), the major metabolite of serotonin (5-HT), in the cerebrospinal fluid of a subgroup of depressed suicide attempters 30 years ago, 7 substantial additional evidence has accumulated that implicates the serotonergic system in both depression and suicide. 3,4,[8][9][10][11] Despite some inconsistencies across these studies and their inability to distinguish between neurobiological factors associated with suicide from those associated with the comorbid mental illness, these findings have raised the possibility of specific suicide-associated differences in various aspects of serotonergic function (for example, receptors, transporters, metabolic enzymes and their functional regulation). Recent studies have suggested abnormalities in mRNA editing of one of the serotonin receptors-2C (5-HT 2C R)-in depressed suicide victims.…”
Section: Introductionmentioning
confidence: 99%
“…Since the demonstration of decreased levels of 5-hydroxyindoleacetic acid (5-HIAA), the major metabolite of serotonin (5-HT), in the cerebrospinal fluid of a subgroup of depressed suicide attempters 30 years ago, 7 substantial additional evidence has accumulated that implicates the serotonergic system in both depression and suicide. 3,4,[8][9][10][11] Despite some inconsistencies across these studies and their inability to distinguish between neurobiological factors associated with suicide from those associated with the comorbid mental illness, these findings have raised the possibility of specific suicide-associated differences in various aspects of serotonergic function (for example, receptors, transporters, metabolic enzymes and their functional regulation). Recent studies have suggested abnormalities in mRNA editing of one of the serotonin receptors-2C (5-HT 2C R)-in depressed suicide victims.…”
Section: Introductionmentioning
confidence: 99%
“…A role for serotonergic function in aggressive and to a lesser extent, impulsive behaviour, is well documented (Ryding et al 2006;Congdon et al 2008), consistent with observations that low SERt binding associated with suicide appears to be concentrated in the ventromedial PFC and anterior cingulate regions, which play a role in mediating inhibition and restraint (Arango et al 1995;Mann et al 2000). However, using post-mortem brain tissue, platelets, and DnA from suicide completers and attempters has not provided unequivocal evidence for a pre-eminent role for the SERt in the pathophysiology of suicide (Purselle and nemeroff 2003).…”
Section: -Ht 2a Receptor In Suicidal Behaviourmentioning
confidence: 66%
“…The serotonin transporter (SERT), located on serotonergic neurons mainly in the dorsal raphe nuclei, is responsible for the modulation of released 5-HT via its reuptake from the extracellular space into presynaptic neurons [115]. Altered SERT has been reported in MDD patients [116][117][118], and has been considered to be involved in the pathophysiology of depression [119] and suicide [115].…”
Section: Pet and Spect Imaging Of Neurotransmittersmentioning
confidence: 99%
“…Altered SERT has been reported in MDD patients [116][117][118], and has been considered to be involved in the pathophysiology of depression [119] and suicide [115]. Recently, a study by Yeh et al [120] …”
Section: Pet and Spect Imaging Of Neurotransmittersmentioning
confidence: 99%